2020
DOI: 10.1002/ehf2.12721
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐aortic balloon pump: is the technique really outdated?

Abstract: Aims Intra-aortic balloon pump (IABP) utilization was expected to be quickly abandoned following the IABP-shock trial and its class III, level B recommendation in the 2016 European Society of Cardiology (ESC) guidelines. The aim of this study was to evaluate the use of IABP compared with other mechanical support devices in a nationwide approach. Methods and results We conducted a retrospective study based on the French national hospital discharge database. All patients undergoing assist device implantation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Although many temporary and permanent circulatory assist devices (extracorporeal membrane oxygenator [ECMO], left ventricular assist devices [LVAD], bi‐ventricular assist devices [BiVAD], Impella heart pump, etc.) have been proposed for the treatment of patients with the perioperative low cardiac output syndrome, the most common device for circulatory support remains the IABP 6–8,14 . The temporary circulatory support in patients undergoing CABG is achieved by IABP for hours or days after insertion with a relatively low complications rate, while the long‐term circulatory support devices are combined with a higher complications rate 5,14–17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many temporary and permanent circulatory assist devices (extracorporeal membrane oxygenator [ECMO], left ventricular assist devices [LVAD], bi‐ventricular assist devices [BiVAD], Impella heart pump, etc.) have been proposed for the treatment of patients with the perioperative low cardiac output syndrome, the most common device for circulatory support remains the IABP 6–8,14 . The temporary circulatory support in patients undergoing CABG is achieved by IABP for hours or days after insertion with a relatively low complications rate, while the long‐term circulatory support devices are combined with a higher complications rate 5,14–17 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, coronary artery by‐pass grafting (CABG) is the most common heart operation which is performed in cardiac surgery centers and the low cardiac output syndrome is the most common indication for using IABP in cardiac surgery patients. Although the new circulatory assist devices were used for circulatory support of patients with acute heart disease, including cardiac surgery patients, benefits of IABP compared with other assistive devices for the management of preoperative or intraoperative low cardiac output syndrome in cardiac surgery is controversial 8 . Preoperative (prophylactic) insertion of IABP in the high‐risk patients due to preoperative acute coronary syndrome (ACS) or unstable CAD patients was reported by many studies and the results showed that complications and mortality rate was similar with intraoperative IABP insertion 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…3 The pharmacological effect of dydrogesterone is more pronounced than that of other progestins. 4 Although it can reduce the concentration of androgen and serum dehydroepiandrosterone sulfate, dydrogesterone does not affect levels of follicle-stimulating hormone, luteinizing hormone, prolactin, and estrogen. 4 Its dose of 10 to 20 mg/d does not inhibit ovulation, so it is more suitable for establishment of the hypothalamus-pituitary-ovarian axis in adolescent girls with amenorrhea.…”
Section: Amenorrhea Evaluation and Managementmentioning
confidence: 99%
“…3 In this study, the median length of time patients received IABP support was 3 days and the median age of randomized patients was 70 years, which is older than optimal for transplant, especially in the setting of salvaged cardiogenic shock. The current reality that IABPs remain frequently used 4 suggests that clinicians continue to see benefits with IABP support on an individual patient basis despite the IABP-SHOCK II trial conclusions.…”
Section: Review Of Cardiogenic Shock After Acute Myocardial Infarctionmentioning
confidence: 99%
“…Although use of the IABP has decreased over the past 10 years, it remains the most common temporary MCS device used in the setting of AMI-CS (approximately 70% of patients) 36,37 . However, despite its frequent use, randomized controlled trials have not shown an associated increase in survival.…”
Section: Cardiogenic Shockmentioning
confidence: 99%